Accounting Profitability and Firm Market Valuation: A Panel Data Analysis - Rahman, Mohd Haseeb Ur; Ibrahim, Mohd Yussoff; Che Ahmad, Ayoib (Universal Publishers, 2017)
Purpose: The relationship between accounting and market measures of firm financial performance is rarely investigated and produced in congruent results in the past.Therefore, this paper aims to investigate the relationship by examining the impact of profitability on firm market value. The profitability ratios like EPS, ROE, and ROA represent accounting while firm market signifies market measures of firm financial performance. Design/methodology/approach: The study selected stratified random sample of 320 nonfinancial Malaysian listed companies for a period of five years from 2010-2014.The paper used pooled OLS with robust standard errors for 1600 observations of the panel data.Findings/ highlights: The study found that ROE has significant while ROA has an insignificant positive association with firm market value.Moreover, the relationship between EPS and firm market value is negative and statistically significant.Practical implications: The results of the study show that investors give value to the firms which maximize return on their equity.Based on these findings, investors, banks, insurance companies, financial institutions can deploy their economic resources.Originality/value: The paper contributes to inconclusive limited literature.Also, the paper provides important insights for shareholders, management of the firms, and other stakeholders.